Targeting RET in patients with RET-rearranged lung cancers: results from the global, multicenter RET registry - Gautschi, Oliver; Warth, Arne; Muley, Thomas (Journal of clinical oncology, 2017)
PurposeIn addition to prospective trials for non-small-cell lung cancers (NSCLCs) that are driven by less common genomic alterations, registries provide complementary information on patient response to targeted therapies. Here, we present the results of an international registry of patients with RET-rearranged NSCLCs, providing the largest data set, to our knowledge, on outcomes of RET-directed therapy thus far.MethodsA global, multicenter network of thoracic oncologists identified patients with pathologically confirmed NSCLC that harbored a RET rearrangement. Molecular profiling was performed locally by reverse transcriptase polymerase chain reaction, fluorescence in situ hybridization, or next-generation sequencing. Anonymized data—clinical, pathologic, and molecular features—were collected centrally and analyzed by an independent statistician. Best response to RET tyrosine kinase inhibition administered outside of a clinical trial was determined by RECIST v1.1.ResultsBy April 2016, 165 patients with RET-rearranged NSCLC from 29 centers across Europe, Asia, and the United States were accrued. Median age was 61 years (range, 29 to 89 years). The majority of patients were never smokers (63%) with lung adenocarcinomas (98%) and advanced disease (91%). The most frequent rearrangement was KIF5B-RET (72%). Of those patients, 53 received one or more RET tyrosine kinase inhibitors in sequence: cabozantinib (21 patients), vandetanib (11 patients), sunitinib (10 patients), sorafenib (two patients), alectinib (two patients), lenvatinib (two patients), nintedanib (two patients), ponatinib (two patients), and regorafenib (one patient). The rate of any complete or partial response to cabozantinib, vandetanib, and sunitinib was 37%, 18%, and 22%, respectively. Further responses were observed with lenvantinib and nintedanib. Median progression-free survival was 2.3 months (95% CI, 1.6 to 5.0 months), and median overall survival was 6.8 months (95% CI, 3.9 to 14.3 months).ConclusionAvailable multikinase inhibitors had limited activity in patients with RET-rearranged NSCLC in this retrospective study. Further investigation of the biology of RET-rearranged lung cancers and identification of new targeted therapeutics will be required to improve outcomes for these patients.